PENGARUH GENDER ANAK DAN KEBIASAAN ORANG TUA MEMBACAKAN BUKU TERHADAP KEMAMPUAN LITERASI AWAL ANAK USIA DINI - Esra Sangelia Sinaga (Jurnal Penelitian dan Pengembangan Pendidikan Anak Usia Dini, 2019)
Literacy is one of the abilities that must be developed from an early age and is referred to as early literacy. There are several factors that can affect a child’s Earl literacy abilities, including the child’s gender and parental involvement, especially the parents’ habit of reading books. The purpose of writing this article is to explain the influence of children’s gender and parents’ habit of reading books with Children to the ability of early childhood literacy. Literature results show that boys need more intense early literacy stimulation than girls. One form of stimulation that can be done to develop children’s early literacy skills is through the involvement of parents by getting used to reading books with children, because children’s literacy experiences first occur in the home environment.